COMPLEMENTIZER AGREEMENT AND SUBJECT CASE IN CHUVASH RELATIVE CLAUSES. - ULUYÜZ, Buğra Oğuzhan (Turkbilig/Turkoloji Arastirmalari Dergisi, 2026)
Chuvash, as a Turkic language, has been overlooked in previous syntax studies. On the other hand, first impressions show that Chuvash language is a dialect with very important syntactic qualities that still do not fit the syntax typologies mentioned above. In the current study, Chuvash relative clauses will be examined, a syntax topic that does not comply with the general Turkic typology. Complementizer Agreement in terms of the distribution of gerundial suffixes used in Chuvash relative clauses, agreement relation between subject and possessive suffix, deficiencies in the phrase structure and placement of Chuvash in Turkic relative clause typology will be mentioned in the research. Accordingly, Chuvash relative clause structures can be categorized within the Turkic relative clause typology. On the other hand, agreement relationship and subject case seem problematic but it is all about Chuvash's unique agreement morphology and phrase structure features. The subject can get both genitive and nominative cases and the possessive suffixes are marked on the noun modified in Chuvash relative clause structures. In addition, the structural features of Chuvash relative clauses and the presence of the possessive suffix on the modified noun suggest that Chuvash is a type A Turkich language. Likewise, some syntactic test conducted in the study shows that these clauses must be lower than CP.